Can different physical education programs produce specific developments in psychological responses and cognitive functions? An ecological intervention in school‐age children. (25th July 2022) - Rodríguez‐Negro, Josune; Pesola, Johannes Arto; Yanci, Javier
Abstract: Aims: The aim of this study was to investigate the effects of physical education (PE) class contents on 6–8 years school‐age children's perceived exertion, psychological responses and cognitive functions. Materials and Methods: These dimensions were measured in 135 children (6.61 ± 0.58 years) before and after an 8‐week different PE intervention programs [i.e. balance intervention program (BIP), game based program (GBP) or drama learning program (DLP)]. Results: With regard to the physical exertion, higher perceived exertion was found in BIP than in GBP and DLP ( p < .01, ES = −0.5 to −1.0, small to moderate). Regarding cognitive functions, children of the GBP and the DLP significantly improved some of the cognitive functions test scores ( p < .01 or 0.05, ES = 0.5 to 1.5, small to large). Conclusion: These results lead us to think that physical activity could be an effective tool for improving children's cognitive functions.